2021
DOI: 10.33233/rbfex.v19i6.4041
|View full text |Cite
|
Sign up to set email alerts
|

Treinamento físico multicomponente aumenta a força, agilidade e equilíbrio dinâmico em mulheres de meia idade

Abstract: The present study aimed to verify the effects of a multicomponent physical training program on the functional capacity of middle-aged women. Thirty-five women (51.8 ± 5.4 years) underwent a multicomponent physical training program for 16 weeks. The volunteers were submitted to anthropometric measurements and a battery of tests adapted to assess their functional capacity. To verify the normality of the data, the Shapiro Wilk test was used and to compare the values before and after the intervention, a paired t t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…Os resultados de Caldas et al (2019) corroboram para afirmação que as mulheres avaliadas apresentam déficit de força, pois as idosas realizaram 17 repetições no teste, nesse estudo os autores investigaram o efeito de 16 semanas de treinamento físico multicomponente em 27 idosas com idade média de 67,8 ± 6,5, elas foram avaliadas pré e pós intervenção, os autores observaram que os indivíduos realizaram 14 repetições pré e 17 repetições após o programa de intervenção, sugerindo que houve uma melhora em suas capacidades físicas. Rosa et al (2019) realizaram uma intervenção por 20 semanas incluindo 18 idosas ativas, praticantes de musculação, com idade média de 61,44 ± 1,88 anos, avaliadas pré e pós intervenção a fim de verificar a força de membros inferiores realizada pelo TSLC.…”
Section: Discussionunclassified
“…Os resultados de Caldas et al (2019) corroboram para afirmação que as mulheres avaliadas apresentam déficit de força, pois as idosas realizaram 17 repetições no teste, nesse estudo os autores investigaram o efeito de 16 semanas de treinamento físico multicomponente em 27 idosas com idade média de 67,8 ± 6,5, elas foram avaliadas pré e pós intervenção, os autores observaram que os indivíduos realizaram 14 repetições pré e 17 repetições após o programa de intervenção, sugerindo que houve uma melhora em suas capacidades físicas. Rosa et al (2019) realizaram uma intervenção por 20 semanas incluindo 18 idosas ativas, praticantes de musculação, com idade média de 61,44 ± 1,88 anos, avaliadas pré e pós intervenção a fim de verificar a força de membros inferiores realizada pelo TSLC.…”
Section: Discussionunclassified
“…Valenti et al [ 8 ] demonstrated that multicomponent training promotes improvements in physically inactive older people’s physical and functional capacities. Although the American College of Sports Medicine and the American Heart Association guidelines for older adults indicate that a training program should present a multicomponent approach, most intervention studies offer training protocols that sometimes develop only muscular strength and/or aerobic capacity [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%